Titanium incorporation in Zn2TiO4 spinel ceramics - Kim, HT; Kim, Y; Valant, M; Suvorov, D (AMER CERAMIC SOC, 2001)
Compositions in the Zn2TiO4 + xTiO(2) system (x = 0-0.43) were synthesized via the solid-state reaction route, using high-purity (greater than or equal to 99.99%) metal-oxide powders. The incorporation of titanium, in the form of TiO2, in Zn2TiO4 spinel ceramics was investigated by analyzing the crystal structure and measuring the dielectric properties, The results of the crystal structure analyses suggested that TiO2 levels of x less than or equal to 0.33 could be incorporated into the Zn2TiO4 spinel at temperatures of T > 945 degreesC, whereas the solid solubility of titanium in Zn2TiO4 decreased for T < 945 degreesC, When x greater than or equal to 0.28, the Zn2Ti3O8 phase formed in the Zn2TiO4 grain interior while cooling after heat treatment. Measurement of the microwave dielectric properties also supported the conclusion that the solubility limit of titanium in Zn2TiO4 was close to x = 0.33, as determined through analysis of the crystal structure.
Keywords: MICROWAVE DIELECTRIC-PROPERTIES; MICROSTRUCTURE